2022
DOI: 10.1001/jamanetworkopen.2022.22009
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Cancer Care During the COVID-19 Pandemic

Abstract: Key Points Question Did racial and ethnic minority adults with cancer in the United States experience more cancer care delays and adverse social and economic effects than White adults during the COVID-19 pandemic? Findings In this survey study of 1240 US adults with cancer, Black and Latinx adults reported experiencing higher rates of delayed cancer care and more adverse social and economic effects than White adults. Meaning This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 47 publications
1
33
2
Order By: Relevance
“…For patients with Medicaid, the observed to expected proportions in 2020 for digestive system, female genital, head and neck, lymphoma, or soft-tissue malignant neoplasms among others were not significantly different from previous years. Whether these findings reflect disparities in cancer prevention, screening, treatment, or outcomes for marginalized groups during the first pandemic year will require further study …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For patients with Medicaid, the observed to expected proportions in 2020 for digestive system, female genital, head and neck, lymphoma, or soft-tissue malignant neoplasms among others were not significantly different from previous years. Whether these findings reflect disparities in cancer prevention, screening, treatment, or outcomes for marginalized groups during the first pandemic year will require further study …”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics of cancer cases in 2020 in the NCDB reflected in some ways previous reports of exposure and access to general medical care during the outset of the pandemic. 4,5,22 The observed to expected proportions decreased for patients diagnosed with cancer in 2020 who were of Asian or Pacific Islander, Hispanic, and non-Hispanic Black race and ethnicity, had lower education and income levels, or had Medicaid or no insurance. However, the observed to expected proportion of patients with private insurance, at highest income levels, and of younger age also decreased.…”
Section: Ncdb Case Characteristics In 2020mentioning
confidence: 99%
See 2 more Smart Citations
“… 22 , 26 , 28 , 29 , 30 , 31 A national United States (US) survey demonstrated that Black and Latinx adults with cancer self‐reported higher rates of cancer treatment delays and affordability of their cancer treatments. 32 Black patients have been disproportionately affected by the COVID‐19 pandemic with higher rates of morbidity and mortality when compared to other racial groups. 33 , 34 , 35 , 36 As Black patients also have proportionally higher rates of late‐stage cancers compared with other races, we hypothesized that the COVID‐19 pandemic would further exacerbate racial disparities in cancer stage at presentation.…”
Section: Discussionmentioning
confidence: 99%